The Effect of Treasury Turnover, Receivable Turnover, Working Capital Turnover and Current Ratio against Profitability Registered Food and Beverage Companies in Indonesia Stock Exchange for the Period 2013 – 2018 - Nelly Nelly; Nagian Toni (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Every company certainly always wants to achieve maximum profitability in carrying out its business activities. This study aims to determine the effect of treasury turnover, accounts receivable turnover, working capital turnover and current ratio on profitability of food and beverage companies listed on the Indonesia Stock Exchange in the period 2013-2018. This research method uses quantitative research methods. This type of research used in this research is quantitative descriptive research. The nature of the research is explanatory research, namely research carried out by explaining or describing the influence exerted on a variable against other variables so that it can know the magnitude of the influence exerted. The population in this study were 22 companies consisting of 6 years. The selection of sampling in this study uses purposive sampling technique that is sampling with certain criteria so that the number of samples taken is 42 samples. The data analysis method used is multiple regression analysis. The results of the hypothesis show that partial treasury turnover and accounts receivable turnover do not affect profitability, but working capital turnover and current ratio affect profitability. Simultaneous testing of treasury turnover, accounts receivable turnover, working capital turnover and current ratio significantly influence profitability. The coefficient of determination is 55.5%, which means that 55.5% of the variation of the dependent variable (profitability) can be explained by the variation of the independent variables in this study.